HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP REMAJA DALAM PENCEGAHAN PENLURAN COVID-19 DI LINGKUNGAN ASRAMA PANTI - Nurhayati, Nurhayati; Wijaya, Andri Kusuma; Setyawati, Asih Dewi (Care : Jurnal Ilmiah Ilmu Kesehatan, 2022)
The number of people infected by the novel coronavirus (COVID‑19) is rapidly increasing worldwide. Recently, Indonesia is one of the countries with a high number of death of patients with COVID-19 in Asia. As the incidence of COVID-19 increases rapidly, it is necessary to prevent the transmission of COVID-19 in a populous area. This study aims to examine the knowledge and attitude among adolescences in preventing COVID-19. This study was a correlational study that was conducted in Panti Sosial Bina Netra, Kota Bengkulu. Knowledge and attitude questionnaires were used in this study. A descriptive and Pearson product-moment was used for data analysis. The study found that the majority of respondents have a good knowledge and attitude. Data analysis also showed that knowledge has a significant relationship with attitude in preventing COVID-19.